Durable complete response after combined treatment with tumor-infiltrating lymphocytes and oncolytic adenovirus (TILT-123) in a patient with metastatic mucosal melanoma - T.J. Monberg; T. Kudling; B. Albieri; S. Pakola; E. Ellebaek; M. Donia; R.L. Eefsen; C. von Buchwald; C. Kistler; J.M. Santos; J. Clubb; L. Haybout; et al. (Immuno-Oncology and Technology)
Background: Despite significant advancements in the treatment of malignant melanoma, metastatic mucosal melanoma remains a therapeutic challenge due to its complex pathogenesis, distinct pathological characteristics, and limited response to immunotherapy. Combining different immunotherapeutic approaches offers a potential strategy to address these challenges. Tumor-infiltrating lymphocyte (TIL) therapy and oncolytic virus therapy represent promising treatment modalities that may synergize with each other. Patient and methods: We present a case of a 48-year-old woman with metastatic sinonasal mucosal melanoma who achieved a durable complete pathological response following treatment with multiple injections of the oncolytic virus TILT-123 (igrelimogene litadenorepvec) and a single infusion of TILs, without preconditioning chemotherapy or postconditioning interleukin-2. Results: Immunohistochemical analysis and single-cell sequencing revealed interesting alterations in injected and noninjected tumors as well as in peripheral blood, during the treatment course, suggesting that TILT-123 facilitated TIL engraftment into the tumor, ultimately leading to a complete response. Conclusions: This case underscores the potential of combined immunotherapeutic approaches as a promising strategy for patients with metastatic mucosal melanoma.